Principles of jet-slit homogenizer of milk with separate supply of cream - Tkach, V.; Kovalov, Oleksandr; Ковальов, Олександр Олександрович; Ковалев, Александр Александрович (My University, 2021)
Homogenization of milk refers to the regulatory operations of technological processes for the production of drinking milk, fermented milk products and beverages, yogurts, mixtures for the production of ice cream and more. With the exception of sterilization and pasteurization, this process is the most energy consuming. The percentage of homogenization among the total electricity consumption of dairy enterprises reaches 25–35%, and the specific energy consumption of the most common valve homogenizers in the industry exceeds 6–7 kWh/t. Therefore, the reduction of energy consumption for homogenization while ensuring a high degree of dispersion of milk fat is an urgent problem of the industry/
Keywords: homogenization; milk; milk emulsion; energy efficiency